A atuação das(os) assistentes sociais nos centros de atenção psicossocial tipo I (CAPSs) em Sergipe - Carvalho, Diléa Lucas de (2019)
This study aims to analyze the performance of social workers in Psychosocial Care Centers tipe I (CAPSs) in Sergipe. To this end, we sought to identify the activities developed by the social workers in the CAPSs; verify, in interdisciplinary work, how the work of the social worker occurs; understand how Social Work professionals orient their work to the Field and Core dimensions and identify the key challenges and difficulties faced by social workers in CAPSs. This is an exploratory study, of qualitative character and that is referenced in the historical-dialectical materialist method. It has as research universe the CAPSs type I of the state of Sergipe, that is, 42 services enabled. From these was taken a sample of 07 equipment located in the regions of Itabaiana (04) and Nossa Senhora da Glória (03), covering 07 municipalities. A total of 05 social workers were interviewed, using the semi-structured interview as an instrument. As a result, it was noticed that there was an increase in the implementation of CAPSs in Sergipe from 2005, which allowed the greater insertion of social workers in the area of mental health. The interviewees are all female, with degrees in the main training institutions of the state, have, on average, 20 years of training and more than one employment relationship. With regard to professional performance, it was found that the activities of social workers endorse the historical demands of the profession, which are expanded by the demands of the mental health model, with professional orientation more focused on the actions of the Center, which incorporate the language of the psychosocial mode, such as the consideration of the bond and the affectivity present in the activities, enunciating approximation with the field perspective and interdisciplinary actions, although it is found that there is a predominance with multidisciplinary actions. Challenges arise from material difficulties, the interdisciplinary approach itself, as well as the profile of users and their relationship with society. With this study, we realized the many possible paths in the analyzes performed, understanding that this research is only a possible clipping of the sample presented, without losing sight of the balance of reality that jumps to the eyes of the set of actors who think the profession of the Service. Social in mental health.